Dual Phase Change Thermal Diodes with High Rectification for Thermal Management near Room Temperature. Issue 5 (28th October 2021) - Kommandur, Sampath; Kishore, Ravi Anant; Booten, Chuck; Cui, Shuang; Wheeler, Lance M.; Vidal, Judith
Abstract: Thermal diodes are passive systems that modulate their thermal resistance depending on the direction of temperature gradient, thereby allowing preferential directional heat flow. A dual phase thermal diode consists of a junction between two phase change materials that have opposing temperature‐dependent thermal conductivity trends, and whose performance (i.e., rectification ratio) is related to the ratio of the thermal conductivities of the different phases. In this work, a dual phase change diode with a rectification ratio of ≈3.5 for an applied temperature bias of ≈40 K is presented, which is among the highest‐performing junction diodes based on phase change materials at the macroscale for near room temperature applications. The diode is composed of an aqueous solution of poly( N ‐isopropylacrylamide), a thermo‐responsive polymer, and calcium chloride hexahydrate—a solid‐liquid phase change material. Experimental insights are provided into the contributions of different heat transfer mechanisms, conduction, and convection, and the effect of concentration of the thermo‐responsive polymer. Abstract : A thermal diode based on two phase change materials with a rectification ratio of 3.5 is demonstrated. The diode is composed of an aqueous solution of poly ( N ‐isopropylacrylamide), a thermo‐responsive polymer, and calcium chloride hexahydrate—a solid‐liquid phase change material. The rectification ratio is the highest among macroscale junction diodes operated near room temperature.